Impact of family-centered education on medication adherence in patients with cardiomyopathy: A clinical trial - Hanieh Gholamnejad; Mahnaz Seyedoshohadaee; Parisa Bozorgzad; Shima Haghani; Raziyeh Omidvar; Fatemeh Kheirkhah (حیات)
Background & Aim: Medication adherence remains a significant challenge in the management of patients with cardiomyopathy, with many patients relying on external support systems to maintain compliance. The study aimed to assess the impact of family-centered educational interventions on medication adherence among patients with cardiomyopathy. Methods & Materials: This controlled clinical trial employed convenience sampling to select 80 patients attending the Heart Failure Clinic at Shahid Rajaee Hospital in Tehran in 2023. Participants were randomly assigned to two groups of 40 each. The intervention consisted of two 30-minute family-centered education sessions delivered to the intervention group, while the control group received standard informational care. Medication adherence was assessed using the Morisky Medication Adherence Scale two weeks post-intervention. Data were analyzed with SPSS version 22, using both descriptive and inferential statistics. Results: The groups were comparable regarding demographic variables and disease characteristics (P>0.05). Prior to the intervention, the mean (±SD) medication adherence scores were 5.00±1.19 for the control group and 4.35±1.05 for the intervention group (P=0.12). Post-intervention, adherence scores improved significantly in the intervention group, with a mean (±SD) of 6.43±0.78 compared to 5.10±1.19 in the control group (P=0.001). Conclusion: Family-centered educational programs can effectively enhance medication adherence in patients with cardiomyopathy. The results highlight the valuable role nurses play in leveraging the potential of family members to provide education and support to patients, ultimately contributing to improved quality of life. Clinical trial registry: IRCT20230216057433N1